Implementasi nilai kemanusiaan dan keadilan Pancasila (Sila 2 & 5) dalam mengatasi rasisme guna memperkuat identitas nasional dan kedaulatan bangsa - Nugroho, FEBRIANTO Andi (Maliki Interdisciplinary Journal, 2025)
Racism remains a significant challenge in Indonesia because it threatens national identity and weakens national unity. Incidents of racial discrimination show that the values of humanity and social justice in Pancasila are not yet fully internalized in society. This article analyzes how the implementation of the values contained in the second principle of Pancasila, “Just and Civilized Humanity,” and the fifth principle, “Social Justice for All Indonesian People,” can serve as a solution to racism while strengthening national identity and state sovereignty. This study uses a literature review method by examining relevant scientific journals, academic articles, and official documents. The results indicate that the second principle promotes respect for human dignity without racial discrimination, while the fifth principle ensures fairness and equality in social opportunity and legal protection. The implementation of both principles not only reduces racism but also reinforces national identity through the cultivation of humanity, unity, and appreciation of diversity. Therefore, Pancasila must be translated into policies, character education, and social culture to build tolerance and preserve national sovereignty. However, social reality shows that the implementation of these values ​​is not yet fully optimal. Social disparities, ethnic stereotypes, and implicit discrimination persist, weakening national integration. Therefore, a comprehensive implementation strategy is needed through collaboration between the government, educational institutions, and civil society to instill the values ​​of humanity and justice sustainably. Pancasila-based education needs to be strengthened not only at the cognitive level, but also at the affective and practical levels, so that these values ​​are truly internalized in the daily behavior of citizens. This study aims to analyze how the actualization of the Second and Fifth Principles can be an effective instrument in preventing racism, strengthening social cohesion, and realizing an inclusive, just, and civilized Indonesian society in accordance with the ideals of Pancasila.